No evidence for significant age spreads in young massive LMC clusters (2015)
ABSTRACT: Recent discoveries have put the picture of stellar clusters being simple stellar populations into question. In particular, the color magnitude diagrams of intermediate age (1–2 Gyr) massive clusters in the Large Magellanic Cloud (LMC) show features that could be interpreted as age spreads of 100–500 Myr. If multiple generations of stars are present in these clusters then, as a consequence, young (<1 Gyr) clusters with similar properties should have age spreads of the same order. In this paper we use archival Hubble Space Telescope (HST) data of eight young massive LMC clusters (NGC 1831, NGC 1847, NGC 1850, NGC 2004, NGC 2100, NGC 2136, NGC 2157 and NGC 2249) to test this hypothesis. We analyzed the color–magnitude diagrams of these clusters and fitted their star formation history to derive upper limits of potential age spreads. We find that none of the clusters analyzed in this work shows evidence for an extended star formation history that would be consistent with the age spreads proposed for intermediate age LMC clusters. Tests with artificial single age clusters show that the fitted age dispersion of the youngest clusters is consistent with spreads that are purely induced by photometric errors. As an additional result we determined a new age of NGC 1850 of ∼100 Myr, significantly higher than the commonly used value of about 30 Myr, although consistent with early HST estimates.